The Relationship between Energy Consumption, Agricultural and Industrial Production, and Economic Growth: ARDL Border Value Approach in the Case of Kazakhstan - Abdibekov, Saken Ualikhanovich; Gridneva, Yelena Evgenevna; Kaliakparova, Gulnar Shaimardanovna; Amankeldi, Nazigul Amankeldikyzy; Perneyeva, Gulmira Amangeldiyevna; Kulbay, Bauyrzhan Susaruly; Myrzabekkyzy, Kundyz (International Journal of Energy Economics and Policy, 2024)
This study analyzes the impact of energy consumption and industrial and agricultural production on economic growth between 2000 and 2022 in Kazakhstan using the ARDL method. The research findings determined that all three variables affect the economic growth of Kazakhstan. Another important finding is that, within the framework of the variables included in the analysis, the model shows that after a shock, the economic structure will recover and regain its footing in a short period, such as 1.5 years. Therefore this study provides important information to Kazakh decision-makers and gives confidence in the solidity of the country's economic structure. The study employs a model that includes industrial production and agricultural production, along with energy consumption on economic growth, as only one variable (index variable). As well known, production and trade as fields of economic activity can also be taken separately. Therefore they can be included in the model separately and their individual effects on GDP can be analyzed. By carrying out studies in this manner, we can identify the determinants of the Kazakh economy and use sample applications to analyze the dynamics of economic growth in general.